Simulation of membrane separations using a modified Maxwell-Stefan model - Brito, Paulo (2010)
A modified Maxwell-Stefan model, which considers both the concentration polarization and the transport through the membrane, is tested for the simulation of Dextran-98000 aqueous solutions filtration. The model is able to successfully simulate experimental data in the high rejection/low flux region, but does replicate the observed rejection drop/pressure build-up which occurs for increased fluxes, which may be due to limitations of the model itself.